Exploratory Analysis and Identification of Factors Challenging Digital Transformation in Bio Farma Group - Ananda Muhammad, Rafi; Noviaristanti, Siska (Publisher Cv. Inara, 2025)
In the era of Industry 4.0, companies must adapt to remain competitive, including through digital transformation. Bio Farma, a leading vaccine manufacturer in Indonesia and the parent of the state-owned pharmaceutical holding (Bio Farma Group), is undergoing such a transformation. This includes subsidiaries like Kimia Farma, Indofarma, and INUKI. To accelerate this process, Bio Farma established the Directorate of Transformation and Digital to coordinate initiatives across all levels of the organization. This study explores and identifies the main challenges in the company’s digital transformation using a mixed-methods approach with an exploratory sequential design. Data were collected from interviews with five key informants and surveys involving 327 employees across the Bio Farma Group. A combination of qualitative and quantitative analysis, including Confirmatory Factor Analysis (CFA), was used to uncover the core challenges. The findings revealed 13 key factors: digital capability, strategy, technology, organization and culture, digital efficiency, digital readiness, customer focus, digital research, investment perception, operations, collaboration, investment review, and digital priority. These challenges extend beyond technical issues to strategic planning, organizational readiness, cultural alignment, collaboration, and investment evaluation. This research provides a strategic reference for managing digital transformation, particularly for state-owned enterprises in the health sector. The results are expected to support Bio Farma Group in formulating effective policies to enhance digital capabilities, strengthen collaboration, improve efficiency, and ensure sustainable digital development.